Market Structure and Industrial Behavior Analysis of Micro, Small and Medium Enterprises (MSMEs) in Indonesia: a Case Study of The Handicraft Industry - Aulia Rahmah (MARAS : Jurnal Penelitian Multidisiplin, 2026)
This study aims to analyze the market structure and industrial behavior of Micro, Small and Medium Enterprises (MSMEs) in the handicraft industry in Indonesia and identify barriers faced by MSMEs in market access and business development. Using a qualitative method with a case study approach, data were collected through in-depth interviews with 15 informants (10 MSME owners, 3 craftsmen, and 2 buyers/distributors) in Yogyakarta and Bali, complemented by direct observation and document analysis. The results show that the handicraft MSME market tends toward monopolistic competition with many producers offering differentiated products. However, significant entry barriers exist related to limited capital, technology, and market access, creating market imperfections. MSME behavior patterns show strong dependence on local markets (100% use physical stores, only 20% utilize e-commerce), cost-plus pricing with 30-50% markup, and limited innovation capacity. This study contributes to understanding industrial economics in the Indonesian MSME context by confirming the Structure-Conduct-Performance (SCP) paradigm and provides policy recommendations including flexible financing schemes, digital literacy programs, industry cluster formation, and strengthening intermediary institutions to improve market efficiency and MSME competitiveness.